Long-term abatement potential and current policy trajectories in Latin American countries - Clarke, L.; McFarland, J; Octaviano, C; Ruijvend, B. van; Beach, Robert H.; Daenzer, Kathryn; Herreras Martínez, S.; Lucena, A; Kitous, A; Labriet, M; Loboguerrero Rodriguez, Ana María; Mundraa, A; et al. (Elsevier, 2016)
This paper provides perspectives on the role of Latin American and Latin American countries in meeting global abatement goals, based on the scenarios developed through the CLIMACAP–LAMP modeling study. Abatement potential in Latin America, among other things, is influenced by its development status, the large contributions of non-CO2 and land use change CO2 emissions, and energy endowments. In most scenarios in this study, the economic potential to reduce fossil fuel CO2 as well as non-CO2 emissions in Latin America in 2050 is lower than in the rest of the world (in total) when measured against 2010 emissions, due largely to higher emission growth in Latin America than in the rest of the world in the absence of abatement. The potential to reduce land use change CO2 emissions is complicated by a wide range of factors and is not addressed in this paper (land use emissions are largely addressed in a companion paper). The study confirms the results of previous research that the variation in abatement costs across models may vary by an order of magnitude or more, limiting the value of these assessments and supporting continued calls for research on the degree to which models are effectively representing key local circumstances that influence costs and available abatement options. Finally, a review of policies in place in several Latin American countries at the time of this writing finds that they would be of varying success in meeting the emission levels proposed by the most recent IPCC reports to limit global temperature change to 2 °C.